Fundamentals of audiology for the speech-language pathologist - Welling, Deborah R.; Ukstins, Carol A. (Burlington, Massachusetts : Jones & Bartlett Learning, 2022)
'Fundamentals of Audiology for the Speech-Language Pathologist is specifically written to provide the SLP with a solid foundational understanding of the hearing mechanism, audiological equipment and procedures, and the diagnosis and (re)habilitation of hearing loss'--
Includes bibliographical references and index.
Keywords: Audiology; Hearing disorders -- Diagnosis